Teori Sikap dan Persuasi: Kajian Literatur Cognitive Dissonance dan Elaboration Likelihood Model - Nabila, Asyifa; Neviyarni, Neviyarni (Lembaga Yasin AlSys, 2026)
Attitude change is an important area of inquiry in social psychology because it relates to individuals’ responses to information and persuasive messages across various communication contexts. This article aims to examine the mechanisms of attitude change through Cognitive Dissonance Theory (CDT) and the Elaboration Likelihood Model (ELM). The study employs a qualitative literature review approach by examining classical and contemporary works from relevant national and international open-access journals on attitude change and persuasion. The findings indicate that CDT explains attitude change as an individual’s attempt to reduce discomfort arising from cognitive conflict when inconsistencies occur between beliefs, attitudes, and behaviours, whereas ELM explains attitude change based on message processing routes, namely the central route involving deep elaboration and the peripheral route relying on simple cues. The integration of these two theories suggests that attitude change is the result of an interaction between internal drives to achieve cognitive consistency and external information-processing mechanisms within the persuasion process. This review provides a theoretical contribution by clarifying the complementary relationship between CDT and ELM in understanding the dynamics of attitude change in social psychology.